(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Liposomal vesicular drug carriers for ocular delivery have earned a wide potential nowadays. Prednisolone Acetate liposome as ocular drug carriers have been demonstrated to be a useful mode to ameliorate bioavailability and patient abidance. Liposome was prepared by lipid extruder method. Liposome were characterized for entrapment efficiency (EE %), vesicle size, surface morphology and in vitro drug release. An ex vivo corneal permeation study was performed to determine the level of drug in the external eye tissue of goat and an ocular irritation assessment was done by Hen’s Egg Test - Chorioallantoic Membrane (HET-CAM) method. The optimized formulation of liposome had shown acceptable viscosity (1.21 ± 0.03 cps), refractive index (1.47±0.001), osmolarity (303 ± 3 mOsm) and pH measurement (7.12 ± 0.09). Liposome as drug delivery carriers were evidenced to be a anticipating impendent to enhance corneal contact and penetration as well as retention time in the eye ensuing in a prolonged action and enhanced bioavailability. The results of stability study exhibited stable profile of developed liposomes.